Modulation of Stretch-Shortening-Cycle Behavior With Eccentric Loading of Triceps Surae: A Possible Therapeutic Mechanism - Debenham, J.; Gibson, W.; Travers, M.; Campbell, A.; Allison, Garry (Human Kinetics Publishers INC, 2016)
Context: Eccentric exercises are increasingly being used to treat lower-limb musculoskeletal conditions such as Achilles tendinopathy. Despite widespread clinical application and documented efficacy, mechanisms underpinning clinical benefit remain unclear. Positive adaptations in motor performance are a potential mechanism. Objective: To investigate how an eccentric loading intervention influences measures of stretch-shortening-cycle (SSC) behavior during a hopping task. Design: Within-subjects repeated-measures observational study. Setting: University motion-analysis laboratory. Participants: Healthy adults. Interventions: A single intervention of 5 sets of 10 eccentric plantar-flexion contractions at 6 repetitions maximum using a commercial seated calf-raise machine. Main Outcome Measures: Lower-limb stiffness, sagittal-plane ankle kinematics, and temporal muscle activity of the agonist (soleus) and antagonist (tibialis anterior) muscles, measured during submaximal hopping on a custom-built sledge-jump system. Results: Eccentric loading altered ankle kinematics during submaximal hopping; peak angle shifted to a less dorsiflexed position by 2.9° and ankle angle precontact shifted by 4.4° (P < .001). Lower-limb stiffness increased from 5.9 to 6.8 N/m (P < .001), while surface EMG measures of soleus occurred 14–44% earlier (P < .001) after the loading intervention. Conclusions: These findings suggest that eccentric loading alters SSC behavior in a manner reflective of improved motor performance. Decreased ankle excursion, increased lower-limb stiffness, and alterations in motor control may represent a positive adaptive response to eccentric loading. These findings support the theory that mechanisms underpinning eccentric loading for tendinopathy may in part be due to improved “buffering” of the tendon by the neuromuscular system.